Acupuncture for Atraumatic Shoulder Conditions: Protocol for a Systematic Review and Meta-Analysis - Wang, Yi; Xu, Yan; Peng, Yu; Liao, Shichuan; Dai, Guogang; Li, Tao (Frontiers in Medicine, 2022)
Shoulder pain is one of the most common musculoskeletal disorders among adults and is caused by a variety of shoulder conditions. The popularity of different acupuncture methods in the nonsurgical treatment of shoulder pain has increased recently. However, evidence regarding the efficacy of acupuncture for shoulder pain is inconsistent, and there is a lack of supporting evidence regarding the overall efficacy of different acupuncture methods for shoulder pain. A systematic review will be conducted to assess the effectiveness of a wide range of acupuncture techniques for atraumatic shoulder conditions. The PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Web of Science, Ovid MEDLINE, Chinese Biomedical Literature, Chinese National Knowledge Infrastructure, Wanfang, and Chongqing VIP databases will be searched to identify eligible studies. Studies will be selected according to preset inclusion and exclusion criteria. Relevant data will be extracted from the final included literature. Heterogeneity, risk of bias, publication bias and evidence quality will be assessed, and subgroup analysis and sensitivity analysis will be performed. Systematic review registration: PROSPERO registration number CRD42021249625.